2020
DOI: 10.3390/ph13100286
|View full text |Cite|
|
Sign up to set email alerts
|

Penetration into Cancer Cells via Clathrin-Dependent Mechanism Allows L-Asparaginase from Rhodospirillum rubrum to Inhibit Telomerase

Abstract: The anticancer effect of L-asparaginases (L-ASNases) is attributable to their ability to hydrolyze L-asparagine in the bloodstream and cancer cell microenvironment. Rhodospirillum rubrum (RrA) has dual mechanism of action and plays a role in the suppression of telomerase activity. The aim of this work was to investigate the possible mechanism of RrA penetration into human cancer cells. Labeling of widely used L-ASNases by fluorescein isothiocyanate followed by flow cytometry and fluorescent microscopy demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Sodium azide (NaN 3 ) is known to inhibit ATP synthesis and thus inhibit endocytosis because endocytosis is an ATP-dependent process [ 61 ]. We studied the influence of sodium azide on the penetration of sRL2 into A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium azide (NaN 3 ) is known to inhibit ATP synthesis and thus inhibit endocytosis because endocytosis is an ATP-dependent process [ 61 ]. We studied the influence of sodium azide on the penetration of sRL2 into A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the highest ranked microorganisms associated to early stage colon cancer (Table 3), we have found that, in the case of Rhodospirillum, for instance, it is known to be able to produce molecules such as L-asparaginase which is a regulator of telomerase activity that has been found able to act on human cancer and immune cells (Zhdanov et al, 2017a , b ; Plyasova et al, 2020 ). Nitrosospira is associated with processes related to ammonia oxidation (Kowalchuk and Stephen, 2001 ) in connection with colon cancer (Bingham et al, 1996 ; Bruce et al, 2000 ; Davis and Milner, 2009 ; O'keefe, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, an asparagine-independent cytotoxicity mechanism was reported specifically for a Rodosprillum rubrum mutant L-ASNase [ 83 ]. In contrast to other bacterial L-ASNases, this RrA variant can penetrate cancer cells via a clathrin receptor-dependent manner resulting in suppression of telomerase activity and asparagine-independent cytotoxicity [ 83 , 84 ].…”
Section: Bacterial L-asnase Used In the Clinic For All Therapymentioning
confidence: 99%